Effect of 3D magnetic perturbations on the plasma rotation in ASDEX Upgrade. (3rd June 2016) - Martitsch, A F; Kasilov, S V; Kernbichler, W; Kapper, G; Albert, C G; Heyn, M F; Smith, H M; Strumberger, E; Fietz, S; Suttrop, W; Landreman, M
Abstract: The toroidal torque due to the non-resonant interaction with external magnetic perturbations (TF ripple and perturbations from ELM mitigation coils) in ASDEX Upgrade is modelled with help of the NEO-2 and SFINCS codes and compared to semi-analytical models. It is shown that almost all non-axisymmetric transport regimes contributing to neoclassical toroidal viscosity (NTV) are realized within a single discharge at different radial positions. The NTV torque is obtained to be roughly a quarter of the NBI torque. This indicates the presence of other important momentum sources. The role of these momentum sources and possible integral torque balance measurements are briefly discussed.